Tinjauan Hukum Pidana Islam terhadap Distribusi Konten Film Bermuatan Unsur Seksualitas melalui Aplikasi Streaming Digital - Aldi Tanjung, Muhammad (Jayapangus Press, 2025)
The development of digital technology has had a major impact on the dissemination of information, including in the entertainment and film industries. One prominent phenomenon is the increasing ease of access to film content containing intimate scenes through digital streaming applications. This study aims to examine how Islamic criminal law views such actions, as well as their relevance to the principles of ḥisbah and ta‘zīr in enforcing public morality. The method used is a normative qualitative study with a legal-theological approach. The data sources used include the Qur'an, Hadith, and the opinions of classical and contemporary scholars on pornography. The results of the study indicate that the distribution of film content containing intimate scenes is prohibited (ḥarām) because it contradicts the maqāṣid al-syarī‘ah, particularly in the aspect of hifẓ al-‘irḍ (preserving honor). In the context of Islamic criminal law, perpetrators may be subject to ta‘zīr sanctions in accordance with the policies of the authorities (ulil amri) in order to protect the interests of the community and prevent further moral decay. This study recommends strengthening Sharia-based regulations in the supervision of digital content, as well as the active role of authoritative Islamic institutions in media ethics education and advocacy.